Axial and transverse compression behaviour of basalt fibre reinforced epoxy composite with aluminium hollow shaft with winding at different angle - Norazirahuda Binti Ismail (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
IN recent year, both researcher and industry are focussing their attention toword the development of sustainble composites, rreinforced with natural fibres. In particular, among the natural fibers (i.e. animal, vegetable or mineral) that can be used as reinforcement, the basalt one represent the most interesting for their properties. The aim of this experiment is to investigate and justify of the machanical propoties, transmission losd, strength of component and quality of basalt fiber reinforced composite on cylindrical structure part by using filament minding method. In the in troduction, mechanical propertie (axial compression and tranverse compression) and the influence of winding angle to angle to the bahaviour of basalt fiber have been reviewed.